2013
DOI: 10.1260/0263-6174.31.5.459
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Selective Adsorption of Substituted Aniline Pollutants from Wastewater

Abstract: ZSM-5 zeolite was used to treat wastewater containing aniline, 2-nitroaniline (2-NA), 3-nitroaniline (3-NA) and 4-nitroaniline (4-NA). Each molecule was removed from aqueous solution by Type I Langmuir adsorption onto ZSM-5. The quantities adsorbed varied greatly due to their shape-selective adsorption within the pores of ZSM-5. Aniline and 4-NA had maximum adsorption amounts of 161 and 265 mg g -1 , respectively, while the maximum amounts of 3-NA and 2-NA were 94.3 and 37.2 mg g -1 , corresponding to reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Compared to other contaminants in groundwater, nitrate plays a vital role in groundwater quality aided with human health issues. The excess concentration of nitrate and continuous consumption of nitrate in groundwater causes serious health diseases on infant and different ages of peoples (Alardhi et al 2020a, Albayati and Doyle 2013Albayati et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other contaminants in groundwater, nitrate plays a vital role in groundwater quality aided with human health issues. The excess concentration of nitrate and continuous consumption of nitrate in groundwater causes serious health diseases on infant and different ages of peoples (Alardhi et al 2020a, Albayati and Doyle 2013Albayati et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained water content data indicated the excellent water separation from oily sludge. The high sulphur content of the recovered fuel (2.032 wt%) indicated that the fuel needed further treatment before its used as a finished fuel 50 , 51 .…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained that a large number of vacant surface sites are available for the adsorption at the beginning. It was also suggested that a strong attractive force occurred between the aniline and it's substituted molecules and the sorbent, and with passage of time, the remaining vacant surface sites are difficult to be occupied due to saturation occurred, and this may also be due to the deficient in the number of available sorption sites at the end of the sorption process (Rabih et al 2007;Albayati and Doyle 2013).…”
Section: Adsorption Isothermmentioning
confidence: 99%